Identifying effect heterogeneity to improve the efficiency of job creation schemes in Germany - Marco Caliendo; Reinhard Hujer; Stephan L. Thomsen (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2005)
Previous empirical studies of job creation schemes in Germany have shown that the average effects for the participating individuals are negative. However, we find that this is not true for all strata of the population. Identifying individual characteristics that are responsible for the effect heterogeneity and using this information for a better allocation of individuals therefore bears some scope for improving programme effciency. We present several stratification strategies and discuss the occurring effect heterogeneity. Our findings show that job creation schemes do neither harm nor improve the labour market chances for most of the groups. Exceptions are long-term unemployed men in West and long-term unemployed women in East and West Germany who benefit from participation in terms of higher employment rates.
Keywords: C13; H43; J68; 330; aktivierende Arbeitsmarktpolitik; Wirkungsforschung; Arbeitsbeschaffungsmaßnahme - Erfolgskontrolle; IAB-Bewerberangebotsdatei; IAB-Maßnahmeteilnehmergrunddatei; Beschäftigtenstatistik; berufliche Reintegration; Langzeitarbeitslose; Arbeitsmarktchancen; Ostdeutschland; Westdeutschland; Bundesrepublik Deutschland; Arbeitsbeschaffung; Wirtschaftspolitische Wirkungsanalyse; Beschäftigungseffekt; Langzeitarbeitslosigkeit; Berufliche Integration; Schätzung; Deutschland